Dynamic patterned electrospun fibres for 3D cell culture - Aladdad, Afnan (2016)
Current culture methods to generate large quantities of cells destined for tissue engineering and regenerative medicine commonly use enzymatic digestion. However, this method is not desirable for subsequent cell transfer to the body due to the destruction of important cell-surface proteins and the risk of enzymatic contamination [1]. Therefore, research has led to the development of thermo-responsive surfaces for the continued culture of mammalian cells, with passaging achieved via a drop in the culture temperature. Recognising that the three-dimensional (3D) culture environment influences the cell phenotype, our aim was to generate a thermo-responsive 3D fibre-based scaffold, using electrospinning, to create an enzyme-free 3D culture surface for mammalian cell expansion that would be suitable for cells destined for the clinic. Thermo-responsive poly (poly (ethylene glycol) methacrylate), poly (PEGMA188), with lower critical solution temperature (LCST) of 26°C has been proposed for use within this thesis. It was used in combination with poly (lactic-co-glycolic acid) (PLGA) and poly (ethylene terephthalate) (PET) polymers in order to create 3D thermo-responsive non-woven electrospun fibrous scaffolds, on which different cell types could be cultured and passaged. Poly (PEGMA188) was prepared by free radical polymerization, and then incorporated with PLGA and PET polymers via four different methods: (i) surface adsorption, (ii) NaOH surface treatment, (iii) surface entrapment and (iv) blend-electrospinning. Blend-electrospinning was chosen over the other methods as it produced nano-PET and micro-PLGA bead-less fibres with responsive behaviour. The biocompatibility was assessed via the adhesion and proliferation of different mammalian cell types, including (i) red fluorescent protein (RFP)-expressing 3T3 fibroblasts, (ii) green fluorescent protein (GFP)-expressing primary immortalized human mesenchymal stem cells (ihMSCs), (iii) human colon adenocarcinoma cells (Caco2) and (iv) primary human corneal stromal stem cells (hCSSCs). The cell viability (Alamar Blue assay) was determined to measure the difference in cell populations adherent to the scaffolds while changing the culture temperature. These thermo-responsive scaffolds were able to support cell adhesion and proliferation at 37°C (hydrophobic surface). Furthermore, it was possible to detach the cells from the scaffolds by decreasing the temperature to 17°C (hydrophilic surface). Irrespective of the concentration of poly (PEGMA188) used, all scaffolds exhibited thermo-responsive proprieties; the cells were viable and proliferated in a similar manner to those cultured on control surfaces (PLGA or PET scaffolds). Finally, the effects of the thermo-responsive polymer and 3D culture environment on the hCSSC phenotype were assessed by quantitative reverse transcription-polymerase chain reaction (RT-qPCR) and immunocytochemistry. The application of 3D environments can promote the reversion of activated corneal stromal cells’ ‘fibroblastic phenotype’ to a desirable quiescent keratocyte phenotype. Therefore, seven thermal and enzymatic passages on responsive 3D scaffolds and 2D TCPS, respectively, were performed. Cell culture on the 3D scaffolds promoted the quiescent keratocyte phenotype, with the increased expression of the keratocyte markers, CD34 and ALDH, and decreased expression of the myofibroblast marker, ACTA2, when compared with cells cultured on the 2D culture flasks. In this thesis, the preparation and application of first generation, biocompatible thermo-responsive fibrous scaffolds are described. The combination of ease of preparation, positive cell response and the expansion of a desirable cell phenotype make the thermo-responsive fibres promising as a new class of materials for application in cell culture. The materials developed and studied in this thesis are believed to represent a significant contribution to the fields of biomaterials and tissue engineering.